Mekanisme Penjualan Produk Tanpa Label Kadaluwarsa Perspektif Ekonomi Islam - Yamunida, Miti (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
The purpose of this study is to describe the perspective of Islamic economics about the mechanism of selling products without an expiration date on the Home Industry Bread Hidayah in the Edge of the City of Bengkulu Hybrids. This study uses descriptive qualitative methods, data collection techniques by means of literature studies and interviews. Data analysis starts with a data reduction display and conclusion. This study concludes that the practice of selling products without an expiry date conducted by the owner of the home industry Roti Hidayah in the Edge of the City of Bengkulu Hybrids has not applied the principle of justice to consumers, namely by not including the expiration date of its business products.